Using Rosetta Stone Application as a Mobile Assited Language Learning (MALL) in EFL: Documentary Study - Ahmad Husein Nst; Sholihatul Hamidah Daulay; Utami Dewi (Scope : Journal of English Language Teaching, 2023)
Current technological developments require students and teachers to increasingly explore their abilities in English using currently available applications. This study focuses on analyzing articles that discuss the use of Rosetta Stone in Language Learning applications in teaching English for Foreign Languages (EFL). The aim of this study is to evaluate the effectiveness of the Rosetta Stone Application in teaching English to speakers of other languages (EFL) using data from a variety of journals.. The method used was descriptive method with Documentary Research Design. Documentary research is a type of scholarly exploration that inspects specific exploration subjects utilizing essential sources like texts and notes. Based on six previous journals from various studies in the world such as Indonesia, Iran, Nigeria and Russia. The data illustrates the fact of using Rosetta Stone based on the research results of six researchers who have been published in journals published around the world. The results that can be drawn based on the research report are the use of the Rosetta Stone application in increasing students' abilities in learning English as a foreign language effectively. There are substantial variations in learning English as a Foreign Language between individuals who have been trained utilizing the Rosetta Stone Application, such as speaking, listening, writing, vocabulary knowledge, and pronunciation.